PENERAPAN METODE TUTOR SEBAYADALAM MENINGKATKAN KREATIVITAS BERMUSIK PESERTA DIDIK PADA MATA PELAJARAN SENI BUDAYADI KELAS VIISMP NEGERI 1 SUKARESMI - Kurniadi, Dedi (Jurnal Budaya Nusantara, 2019)
This study aims to analyze the reality of improving the students’ musical creativity through peer tutor on arts and culture lesson at VII grade, State Junior High School 1 Sukaresmi. Quasi experiment with statistical test is used in this study. The result of the study shows that peer tutor significantly improves the students’ musical creativity compared to that of conventional method. This improvement can be seen from the control class which uses conventional method showing average score of 60.7 and the experiment class which uses peer tutor method showing the higher average score of 79.7.